Unlocking the Combination: Potentiation of Radiation-Induced Antitumor Responses with Immunotherapy - Wattenberg, Max M. (2014)
There is increasing evidence of the potential for radiation therapy to generate antitumor immune responses. The mechanisms of this immune-activating potential include actions on tumor cells such as immunogenic cell death and phenotypic change. Radiation modulates tumor cell surface expression of cell death receptors, tumor-associated antigens and adhesion molecules. This process of immunomodulation sensitizes tumor cells to immune-mediated killing. Radiation also affects immune compartments, including antigen-presenting cells, cytotoxic T lymphocytes and humoral immunity, leading to specific antitumor immune responses. Recognizing the importance of immunity as a potentiator of response to radiation leads to rational augmentation of antitumor immunity by combining radiation and immunotherapy. Targeted immunotherapy manipulates the immune system in a way that best synergizes with radiation. This article discusses the ability of radiation monotherapy to induce antitumor immunity, with a focus on the effect of radiation on antigen-presenting cells and cytotoxic T lymphocytes. We define two important responses generated by tumor cells, immunogenic cell death and immunomodulation, both of which are radiation dose-dependent. In conclusion, we describe the translation of several combination therapies from the preclinical to the clinical setting and identify opportunities for further exploration.